Structure and drivers of ocean mixing north of Svalbard in summer and fall 2018 - Koenig, Zoe Charlotte; Kolås, Eivind Hugaas; Fer, Ilker (Copernicus Publications, 2021)
The Arctic Ocean is a major sink for heat and salt for the global ocean. Ocean mixing contributes to this sink by mixing the Atlantic- and Pacific-origin waters with surrounding waters. We investigate the drivers of ocean mixing north of Svalbard, in the Atlantic sector of the Arctic, based on observations collected during two research cruises in summer and fall 2018. Estimates of vertical turbulent heat flux from the Atlantic Water layer up to the mixed layer reach 30 W m−2 in the core of the boundary current, and average to 8 W m−2, accounting for ∼1 % of the total heat loss of the Atlantic layer in the region. In the mixed layer, there is a nonlinear relation between the layer-integrated dissipation and wind energy input; convection was active at a few stations and was responsible for enhanced turbulence compared to what was expected from the wind stress alone. Summer melting of sea ice reduces the temperature, salinity and depth of the mixed layer and increases salt and buoyancy fluxes at the base of the mixed layer. Deeper in the water column and near the seabed, tidal forcing is a major source of turbulence: diapycnal diffusivity in the bottom 250 m of the water column is enhanced during strong tidal currents, reaching on average 10−3 m2 s−1. The average profile of diffusivity decays with distance from the seabed with an e-folding scale of 22 m compared to 18 m in conditions with weaker tidal currents. A nonlinear relation is inferred between the depth-integrated dissipation in the bottom 250 m of the water column and the tidally driven bottom drag and is used to estimate the bottom dissipation along the continental slope of the Eurasian Basin. Computation of an inverse Froude number suggests that nonlinear internal waves forced by the diurnal tidal currents (K1 constituent) can develop north of Svalbard and in the Laptev and Kara seas, with the potential to mix the entire water column vertically. Understanding the drivers of turbulence and the nonlinear pathways for the energy to turbulence in the Arctic ...